Sanksi Hukum Terhadap Hakim Pelanggar Kode Etik Profesi Hakim - Adis Suciawati; Soefyanto Soefyanto (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2019)
Abstract:This study aims to determine the legal sanctions against judges who violate the Code of Ethics and the Code of Conduct for Judges within the scope of the court, especially in the case of trying one's own siblings (cousins). The problem examined in this study regarding the Legal Sanctions Against Judges Violating the Professional Ethics Code of Judges at the Kupang District Court (Judge Rizet Benyamin Rafael Case Study). This research uses the normative method by conducting research using library legal materials by searching library materials or secondary data from primary legal materials, secondary legal materials, and tertiary legal materials. The method of approach is to use the Joint Supreme Court Regulatory approach with the Judicial Commission and the case approach. In data analysis using qualitative analysis, namely by analyzing the starting point on the documentation of various events, information in the form of cases, and written documentation.Keywords: Legal Sanctions Against Judges Violating the Professional Ethics Code of Judges